Cu-containing austenitic stainless steel castings
A Cu-containing austenitic stainless steel slab with controlled chemical composition and microstructure prevents internal cracks during hot rolling by limiting high Cu concentration regions and enhancing equiaxed crystal ratio, ensuring excellent cold workability and hydrogen embrittlement resistance.
Patent Information
- Application Number
- JP2020071491
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-04-13
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2040-04-13
AI Technical Summary
Cu-containing austenitic stainless steel slabs are prone to internal cracks during hot rolling due to macrosegregation, which is influenced by Cu concentration, Mn concentration, and Ni concentration, and existing methods to control water content during casting are insufficient.
A Cu-containing austenitic stainless steel slab with specific chemical composition and controlled microstructural parameters, including limited concentrations of C, Si, Mn, P, S, Cr, Ni, Mo, Cu, and N, and controlled ratios of Cr eq /Ni eq , with regions of high Cu concentration limited to an equivalent diameter of 1.5 mm or less and β value of 2.51 or less, and an equiaxed crystal ratio of over 30%, produced through continuous casting with controlled cooling and electromagnetic stirring.
The solution effectively suppresses internal cracks during hot working while maintaining excellent cold workability and hydrogen embrittlement resistance, enabling the production of high-strength, non-magnetic stainless steel suitable for high-pressure hydrogen environments.
Smart Images

Figure 0007657026000001 
Figure 0007657026000002 
Figure 0007657026000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a Cu-containing austenitic stainless steel cast slab. [Background technology]
[0002] Stainless steel has a wide range of applications due to its excellent corrosion resistance. In the manufacturing process of stainless steel, Cu is sometimes added to improve cold workability. Examples of technologies for improving cold workability by adding Cu include the following:
[0003] For example, Patent Document 1 discloses an austenitic stainless steel that has excellent hydrogen embrittlement resistance and contains 0.10 to 3.00 mass % of Cu as an optional element in order to improve cold workability.
[0004] Patent Document 2 also describes a method for producing a stainless steel having a predetermined chemical composition by cold working at a working ratio of 10 to 20%, followed by cold forging or header processing at a temperature range of 60 to 150°C, and then holding the steel at a temperature range of 300 to 550°C for 15 minutes or more, which results in a 0.2% yield strength of 650 N / mm 2 Tensile strength is 800N / mm 2 A high-strength nonmagnetic steel for fastening superconducting coils of linear motor cars having the above-mentioned characteristics and a magnetic permeability of 1.05 or less is disclosed. The stainless steel used in the technology disclosed in Patent Document 2 contains 1.0 to 4.0 mass % Cu to reduce the work hardening index and suppress the occurrence of cracks during cold working.
[0005] Patent Document 3 discloses a method for producing a Cu-containing stainless steel slab, which is characterized by strengthening cooling of the crater end portion so that the grain size of the Cu alloy phase in the center of the slab becomes 50 μm or less when continuously casting stainless steel containing 1 to 5 mass % Cu. In the method for producing a Cu-containing stainless steel slab disclosed in Patent Document 3, the guideline for the specific water amount of cooling water sprayed on the crater end portion is 0.2 to 0.5 L / (kg-steel). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2016-14180 A [Patent Document 2] Japanese Patent Application Publication No. 9-272954 [Patent Document 3] JP 2000-225441 A Summary of the Invention [Problem to be solved by the invention]
[0007] Cu improves cold workability but reduces hot workability. In the techniques disclosed in Patent Documents 1 and 2, the upper limit of the Cu content is specified to suppress the deterioration of hot workability. However, internal cracks may occur during hot rolling due to macrosegregation of the slab.
[0008] In addition, the manufacturing method of Cu-containing stainless steel slabs disclosed in Patent Document 3 may cause internal cracks during hot rolling if the slab contains Cu and a large amount of Mn, which lowers the solid solubility limit of Cu. Also, the method of controlling the specific water content at the crater end may not be sufficient to prevent internal cracks during hot rolling depending on the casting conditions.
[0009] The present invention has been made in view of the above problems, and an object of the present invention is to provide a Cu-containing austenitic stainless steel cast slab capable of suppressing the occurrence of internal cracks during hot working. [Means for solving the problem]
[0010] The inventors discovered that internal cracks occurring during hot rolling of Cu-containing austenitic stainless steel are caused by liquefaction of areas with high Cu concentration, and that liquefaction within the slab is affected not only by the Cu concentration, but also by the Mn concentration, which reduces the solubility of Cu, and the Ni concentration, which increases the solubility of Cu.
[0011] The present inventors further discovered that even if there are many regions that are prone to liquefaction inside a cast slab, if the area of each of these regions is small, they will not become the starting point of internal cracks, but if the area of each region is large, that region will become the starting point of internal cracks.
[0012] The gist of the present invention, which has been completed based on the above findings, is as follows. [1] In mass%, C: 0.25% or less, Si: 3.0% or less, Mn: 0.1 to 20.0%, P: 0.045% or less, S: 0.0050% or less, Cr: 10.0-25.0%, Ni: 4.0-22.0%, Mo: 5.0% or less Cu: 0.1 to 4.0%, and N: 0.4% or less, with the remainder being Fe and impurities, Cr represented by the following formula (1) eq and Ni represented by the following formula (2) eq Ratio to Cr eq / Ni eq is less than 1.48, In the center of the thickness direction in the casting direction cross section at the center of the width direction, the region where the α value shown by the following formula (3) exceeds 3.63 exists, The above-mentioned area The equivalent circular diameter is 1.5 mm or less, A Cu-containing austenitic stainless steel cast slab, having a β value, as represented by the following formula (4), of 2.51 or less. Cr eq =Cr+(1.37×Mo)+(1.5×Si)…Formula (1) Ni eq =Ni+(0.31×Mn)+Cu+(22×C)+(14.2×N)…Formula (2) α=[Cu]+(0.136×[Mn])-(0.2×[Ni]) …Equation (3) β = Cu+(0.0075×Mn 2 )+(0.0404×Mn)-(0.09×Ni) … Equation (4) In the above equations (1), (2) and (4), Cr, Mo, Si, Ni, Mn, Cu, C, and N represent the content (mass %) of each element. In Equation (3), [Cu], [Mn] and [Ni] are the concentrations (mass %) of each element measured by an electron beam microanalyzer at the center of the thickness direction. [2] The Cu-containing austenitic stainless steel slab according to [1], having an equiaxed crystal ratio of more than 30%. [3] Instead of a part of Fe, in mass %, Al: 0.15% or less, Ca: 0.005% or less, and B: 0.005% or less, The Cu-containing austenitic stainless steel slab according to [1] or [2], containing one or more selected from the group consisting of [4] Instead of a part of Fe, in mass %, Nb: 0.3% or less, or Ti: 0.3% or less, The Cu-containing austenitic stainless steel slab according to any one of [1] to [3], containing at least one of the above.
Advantages of the Invention
[0013] As described above, according to the present invention, it is possible to provide a Cu-containing austenitic stainless steel slab capable of suppressing the occurrence of internal cracks during hot working.
Embodiments for Carrying Out the Invention
[0014] <Cu-containing austenitic stainless steel slab> The Cu-containing austenitic stainless steel cast slab according to the present embodiment contains, by mass%, C: 0.25% or less, Si: 3.0% or less, Mn: 0.1 to 20.0%, P: 0.045% or less, S: 0.0050% or less, Cr: 10.0 to 25.0%, Ni: 4.0 to 22.0%, Mo: 5.0% or less, Cu: 0.1 to 4.0%, and N: 0.4% or less, with the remainder being Fe and impurities, and has a Cr content represented by the following formula (1): eq and Ni represented by the following formula (2) eq Ratio to Cr eq / Ni eq is less than 1.48, and in the thickness direction center of the casting direction cross section at the width direction center, the circle equivalent diameter of a region where the α value represented by the following formula (3) exceeds 3.63 is 1.5 mm or less, and the β value represented by the following formula (4) is 2.51 or less. Cr eq =Cr+(1.37×Mo)+(1.5×Si)…Formula (1) Ni eq =Ni+(0.31×Mn)+Cu+(22×C)+(14.2×N)…Formula (2) α=[Cu]+(0.136×[Mn])-(0.2×[Ni]) …Equation (3) β = Cu + (0.0075 × Mn 2 )+(0.0404×Mn)-(0.09×Ni)…Formula (4) In the above formulas (1), (2), and (4), Cr, Mo, Si, Ni, Mn, Cu, C, and N indicate the content (mass%) of each element, and in the above formula (3), [Cu], [Mn], and [Ni] are the concentrations (mass%) of each element measured at the center in the thickness direction by an electron beam microanalyzer with a beam diameter of 50 μm. The Cu-containing austenitic stainless steel cast slab according to this embodiment will be described in detail below.
[0015] [Chemical composition] First, the chemical components of the Cu-containing austenitic stainless steel cast slab according to this embodiment will be described. Note that % indicating the components means % by mass.
[0016] C (carbon): 0.25% or less C is an element effective in stabilizing the austenite phase, but excessive C content may cause Cr carbides to precipitate, forming a Cr-depleted layer, and reducing corrosion resistance. For this reason, the C content is set to 0.25% or less. The C content is preferably 0.10% or less. On the other hand, C contributes to increasing the strength of the steel material by solid solution strengthening, and also contributes to improving hydrogen embrittlement resistance by suppressing the generation of processing-induced martensite phase through stabilization of the austenite phase. For this reason, the C content is preferably 0.01% or more. The C content is more preferably 0.015% or more.
[0017] Si (silicon): 3.0% or less Although Si is an effective element for stabilizing the austenite phase, excessive Si content promotes the formation of intermetallic compounds such as sigma phase, resulting in a decrease in hot workability and toughness. Therefore, the Si content is set to 3.0% or less. The Si content is preferably 1.0% or less, and more preferably 0.7% or less. On the other hand, Si stabilizes the austenite phase, suppressing the formation of processing-induced martensite phase and improving hydrogen embrittlement resistance, so the Si content is preferably 0.2% or more. The Si content is more preferably 0.4% or more.
[0018] Mn (manganese): 0.1% to 20.0% Mn is an element effective in stabilizing the austenite phase, but if an excessive amount of Mn is contained, the formation of coarse MnS inclusions is promoted, leading to a decrease in the ductility of the austenite phase. In addition, an excessive amount of Mn promotes the formation of nitrides. Therefore, the Mn content is set to 20.0% or less. The Mn content is preferably 10.0% or less. On the other hand, in order to stably obtain the austenite stabilizing effect of Mn, the Mn content is set to 0.1% or more. The Mn content is preferably 1.0% or more, and more preferably more than 2.0%.
[0019] P (phosphorus): 0.045% or less P is contained as an impurity in the Cu-containing austenitic stainless steel slab according to this embodiment. P is an element that reduces hot workability. Therefore, in the Cu-containing austenitic stainless steel slab according to this embodiment, the P content is set to 0.045% or less. The P content is preferably 0.035% or less. Since it is preferable to reduce the P content as much as possible, no lower limit is set, but an extreme reduction leads to an increase in steelmaking costs. Therefore, the P content is preferably 0.008% or more.
[0020] S (sulfur): 0.0050% or less S is an element that segregates at the austenite grain boundaries when a slab is hot worked, weakening the bonding strength of the grain boundaries and inducing cracks during hot working. In order to prevent cracks during hot working, the S content is set to 0.0050% or less. The S content is preferably 0.0010% or less. Since it is preferable to reduce the S content as much as possible, no lower limit is set, but extreme reduction leads to an increase in steelmaking costs. Therefore, the S content is preferably 0.0001% or more.
[0021] Cr (chromium): 10.0 to 25.0% Cr is an essential element for obtaining the corrosion resistance required for stainless steel. Cr also contributes to increasing the strength of austenitic stainless steel. To obtain the above effect, the Cr content is set to 10.0% or more. The Cr content is preferably 13.0% or more. On the other hand, if an excessive amount of Cr is contained, the grain boundary precipitation of Cr-based carbonitrides is promoted, and the corrosion resistance and toughness are reduced. For this reason, the Cr content is set to 25.0% or less. The Cr content is preferably 18.0% or less.
[0022] Ni (nickel): 4.0 to 22.0% Ni forms intermetallic compounds together with Fe, Cr, Mo, or Si, and contributes to high strength, so the Ni content is set to 4.0% or more. Ni also contributes to improving the hydrogen embrittlement resistance of austenitic stainless steel. From the viewpoint of improving hydrogen embrittlement resistance, the Ni content is preferably 4.0% or more. By eliminating component segregation, these effects are further improved, so the Ni content is preferably 11.5% or more. On the other hand, an excessive amount of Ni increases material costs, so the Ni content is set to 22.0% or less. The Ni content is preferably 14.0% or less.
[0023] Mo (molybdenum): 5.0% or less Mo is an element that contributes to increasing the strength and corrosion resistance of austenitic stainless steel. However, the inclusion of Mo leads to an increase in alloy costs. Therefore, the Mo content is set to 5.0% or less. The Mo content is preferably 0.5% or less. On the other hand, Mo is an element that is inevitably mixed in from scrap raw materials. Since it is preferable to reduce the Mo content as much as possible, no lower limit is set, but excessive reduction of the Mo content leads to restrictions on the melting raw materials and increases the manufacturing cost. Therefore, in order to achieve both the above effects and manufacturability, the Mo content is preferably 0.05% or more.
[0024] Cu (copper): 0.10 to 4.0% Cu is an element effective in stabilizing the austenite phase. Cu also contributes to increasing strength through Cu precipitation strengthening. Cu also improves the cold workability and hydrogen embrittlement resistance of the cast slab. On the other hand, if an excessive amount of Cu is contained, the strength of the austenite phase decreases, and the hot workability decreases. Therefore, the Cu content is set to 4.0% or less. The Cu content is preferably 3.55% or less. In order to obtain excellent cold workability and hydrogen embrittlement resistance, the Cu content is 0.10% or more. The Cu content is preferably 1.5% or more.
[0025] N (nitrogen): 0.4% or less N is an element effective for stabilizing the austenite phase, improving corrosion resistance, solid solution strengthening, and precipitation hardening of Cr-based nitrides, but excessive N content promotes excessive generation of Cr-based nitrides, reducing the corrosion resistance, toughness, and hydrogen embrittlement resistance of the austenite phase. For this reason, the N content is set to 0.4% or less. The N content is more preferably 0.35% or less. On the other hand, in order to obtain the above-mentioned effects, the N content is preferably 0.01% or more. The N content is more preferably 0.04% or more.
[0026] The Cu-containing austenitic stainless steel slab according to the present embodiment is composed of Fe and impurities other than the above-mentioned elements, but preferably contains the following elements. The impurities referred to here mean components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes when industrially manufacturing the Cu-containing austenitic stainless steel slab according to the present embodiment, and are permissible within a range that does not adversely affect the present invention. Examples of impurities include Pb, Sn, Zn, Bi, As, Sb, V, Ta, Co, W, Mg, and O (oxygen). The impurity contents are, for example, at levels that are acceptable if Pb is 5 ppm or less, Sn is 0.03% or less, Zn is 10 ppm or less, Bi is 5 ppm or less, As is 100 ppm or less, Sb is 50 ppm or less, V is 0.3% or less, Ta is 0.02% or less, W is 0.3% or less, Co is 0.5% or less, Mg is 30 ppm or less, and O is 100 ppm or less.
[0027] The Cu-containing austenitic stainless steel cast slab according to this embodiment preferably contains the following elements in place of a portion of Fe, as necessary.
[0028] One or more selected from the group consisting of Al (aluminum): 0.15% or less, Ca (calcium): 0.005% or less, and B (boron): 0.005% or less Al, Ca, and B are elements effective in improving deoxidation and hot workability and corrosion resistance of cast slabs. It is preferable that one or more elements selected from these elements are contained as necessary. However, excessive content of the above elements leads to a significant increase in manufacturing costs. For this reason, it is preferable that the Al content is 0.15% or less, the Ca content is 0.005% or less, and B: 0.005% or less. However, in order to obtain a sufficient deoxidation effect, it is preferable to contain one or more of Al: 0.01% or more, Ca: 0.001% or more, and B: 0.001% or more. Note that Al may be contained as an impurity at 0.003% or less, and B and Ca may be contained as impurities at 0.0005% or less.
[0029] At least one of Nb: 0.3% or less or Ti: 0.3% or less Ti and Nb dissolve in steel or precipitate as carbonitrides to increase strength. Therefore, one or two selected from Nb and Ti may be contained as necessary. In this case, the Nb content and the Ti content are preferably 0.3% or less. From the viewpoint of obtaining the above effects of Nb or Ti, the Nb content and the Ti content are preferably 0.01% or more, more preferably 0.05% or more, and further preferably 0.1% or more.
[0030] In the Cu-containing austenitic stainless steel cast slab of the present invention, the balance other than the above-mentioned elements is Fe and impurities, but elements other than the above-mentioned elements can also be contained within a range that does not impair the effects of this embodiment.
[0031] [Cr eq / Ni eq : Less than 1.48] In the Cu-containing austenitic stainless steel slab according to the present embodiment, the above-mentioned chemical components are contained, and the Cr content calculated by the following formulas (1) and (2) is eq and Ni eq Ratio of Cr eq / Ni eq It is important to keep it below 1.48.
[0032] Cr eq =Cr+(1.37×Mo)+(1.5×Si)…Formula (1) Ni eq =Ni+(0.31×Mn)+Cu+(22×C)+(14.2×N)…Formula (2) In the formulas (1) and (2), Cr, Mo, Si, Ni, Mn, Cu, C, and N represent the content (mass%) of each element in the cast slab.
[0033] Cr eq / Ni eq If the Cr content is less than 1.48, the molten steel will solidify in austenite phase when cooled, resulting in austenite phase stainless steel. eq / Ni eq If the Cr content is 1.48 or more, the molten steel is cooled in the two-phase state of austenite and ferrite, and becomes stainless steel containing these two phases. eq / Ni eq is less than 1.48. eq / Ni eq is preferably less than 1.35.
[0034] [The circle equivalent diameter of the area in the thickness direction center in the casting direction cross section at the width direction center where the α value exceeds 3.63 is 1.5 mm or less] In the Cu-containing austenitic stainless steel cast slab according to this embodiment, at the center in the thickness direction in the casting direction cross section at the center in the width direction, the equivalent circle diameter of a region where the α value exceeds 3.63 is 1.5 mm or less.
[0035] The α value is calculated by the following formula (3). α=[Cu]+(0.136×[Mn])-(0.2×[Ni]) …Equation (3) In formula (3), [Cu], [Mn], and [Ni] are the concentrations (mass%) of each element measured at the center in the thickness direction by an electron probe micro analyzer (EPMA).
[0036] Mn is an element that makes Cu easier to liquefy, and Ni is an element that makes Cu more difficult to liquefy. Mn is an element that reduces the amount of Cu that can be dissolved in the gamma phase, and has the effect of promoting Cu precipitation and lowering the melting point of Cu. Therefore, Mn makes Cu easier to precipitate and liquefy. Ni has the effect of increasing the amount of Cu that can be dissolved in the gamma phase, and prevents Cu precipitation at a low melting point. Therefore, Ni makes liquefaction by Cu less likely to occur.
[0037] In the region where the α value exceeds 3.63, Cu is likely to liquefy. If the area of such a region becomes large, cracks are likely to occur. Therefore, the circle equivalent diameter of the region where the α value exceeds 3.63 is set to 1.5 mm or less. In the following, the region where the α value exceeds 3.63 and the circle equivalent diameter exceeds 1.5 mm is referred to as the "semi-macro segregation region."
[0038] With regard to the center in the thickness direction in the casting direction cross section at the center in the width direction, the casting direction cross section at the center in the width direction refers to a cross section cut in the casting direction at a position W / 2 from the end of the width direction of the slab, where W is the width of the slab. The center in the thickness direction refers to a rectangular region with a length in the thickness direction of the slab and a length in the casting direction of 25 mm, whose center is located at a position 1 / 2 of the thickness of the slab in the cross section. In the EPMA analysis, the center in the thickness direction in the casting direction cross section at the center in the width direction is analyzed.
[0039] The EPMA analysis was performed at an acceleration voltage of 15 kV and a probe current of 3.25 × 10 7A, beam diameter 50μm, step 50μm, irradiation time per step 40msec, 500×500 points in the above 25mm square range. EPMA analysis is used to identify the area where the α value is greater than 3.63. EPMA measures the concentrations of Cu, Ni and Mn at each measurement point, so the α value for each measurement point can be calculated. Therefore, the area obtained by connecting the measurement points where the α value is greater than 3.63 is considered to be the area where the α value is greater than 3.63. Note that when the measurement points where the α value is greater than 3.63 are connected, there are cases where the measurement points where the α value is 3.63 or less are included in the area obtained by connecting the measurement points where the α value is greater than 3.63. In such cases, the area excluding the measurement points where the α value is 3.63 or less is considered to be the area where the α value is greater than 3.63. Then, the circle-equivalent diameter of the identified region is calculated. When the measurement points with an α value of more than 3.63 are connected, if a measurement point with an α value of 3.63 or less is included in the region obtained by connecting the measurement points with an α value of more than 3.63, the circle-equivalent diameter is calculated excluding the region with an α value of 3.63 or less.
[0040] [β value: 2.51 or less] The Cu-containing austenitic stainless steel cast slab according to this embodiment has a β value calculated by the following formula (4) of 2.51 or less.
[0041] β = Cu + (0.0075 × Mn 2 )+(0.0404×Mn)-(0.09×Ni)…Formula (4) In formula (4), Cu, Mn, and Ni are the contents (mass%) of each element in the cast slab.
[0042] If the β value exceeds 2.51, semi-macro segregation occurs, and cracks occur in the semi-macro segregation. Therefore, the β value is set to 2.51 or less.
[0043] [Equiaxed crystallinity: over 30%] The equiaxed crystal ratio of the Cu-containing austenitic stainless steel slab according to this embodiment is preferably more than 30%. The equiaxed crystal ratio is defined as the thickness of the equiaxed crystal part relative to the thickness of the slab at the position of 1 / 2 of the width direction of the surface (C cross-section) obtained by cutting the slab in a plane perpendicular to the casting direction. The presence or absence of equiaxed crystals is determined from the macrostructure of the C cross-section. The macrostructure is revealed by the hydrochloric acid method recommended for stainless steel in accordance with JIS G 0553:2019. In the hydrochloric acid method, hydrochloric acid with a concentration of 20% by mass is heated to 70 °C and the stainless steel is immersed and corroded. The corrosion time (immersion time) is 40 minutes.
[0044] Equiaxed crystals are isotropic crystal structures without a specific directionality and are observed in the central part of the macrostructure of the C cross-section. Equiaxed crystals are clearly distinguishable from the chill crystals and columnar crystals existing outside thereof in the C cross-section.
[0045] If the equiaxed crystal ratio is more than 30%, the central segregation of Cu can be suppressed. Therefore, the equiaxed crystal ratio is preferably more than 30%. As long as the equiaxed crystal ratio is more than 30%, for example, it may be 40% or more, or may be 50% or more. On the other hand, the upper limit of the equiaxed crystal ratio is not particularly limited and may be 80% or less, or may be 70% or less.
[0046] <Manufacturing method of Cu-containing austenitic stainless steel slab> Subsequently, the manufacturing method of the Cu-containing austenitic stainless steel slab described above will be explained. The manufacturing method of the Cu-containing austenitic stainless steel slab described below is merely an example, and it may be manufactured by other methods.
[0047] The Cu-containing austenitic stainless steel slab according to this embodiment is produced by continuous casting. In detail, molten stainless steel having the above-mentioned chemical components is produced by a known method, and the molten steel is supplied to a tundish. The molten steel contained in a ladle is supplied to the tundish, and the molten steel is supplied into the mold from a nozzle extending from the lower end of the tundish toward the mold. The molten steel is cooled in the mold (primary cooling), and the molten steel withdrawn from the mold is cooled by a secondary cooling zone arranged below the mold to produce a slab.
[0048] The withdrawal speed Vc of the molten steel from the mold is set to 0.4 to 0.6 m / min, and the superheat ΔT of the molten steel is set to 20 to 40°C. The superheat ΔT is the degree of superheat from the melting point of the steel, and can be obtained by measuring the temperature of the molten steel in the tundish. If the superheat ΔT is 20 to 40°C, fine equiaxed grains are generated, and Cu segregation can be suppressed.
[0049] In the secondary cooling zone, spray cooling is performed by spraying water onto the molten steel. The specific water amount, or the amount of water per 1 kg of molten steel, is 3 to 5 L / (kg-steel), and spray cooling is performed until the temperature at the center of the slab's thickness direction falls below 800°C. If the specific water amount is 3 to 5 L / (kg-steel), a large reduction in central segregation and an increase in the cooling rate can be achieved, suppressing the precipitation and growth of Cu, resulting in a slab that is advantageous in preventing Cu liquefaction. In addition, by continuing spray cooling until the temperature at the center of the slab's thickness direction falls below 800°C, it is possible to suppress fine internal cracks that occur when the slab surface expands due to thermal recovery.
[0050] In the secondary cooling zone, a strand electromagnetic stirrer may be used to stir the molten steel inside the slab in a non-contact manner. The strand electromagnetic stirrer is used to stir the molten steel in a portion where the solid fraction in the thickness direction cross section of the slab is 0.5 to 0.75. The stirring mode is to apply electromagnetic force to each of a pair of long sides in the thickness direction cross section of the slab so that the molten steel in the vicinity of each long side flows in the same direction. The electromagnetic force application pattern is, for example, a pattern in which an electromagnetic force is applied for 6 seconds and then removed for 1 second, and the operation is repeated. By applying the strand electromagnetic stirrer to the secondary cooling zone as described above, the equiaxed crystal fraction of the slab can be improved. As a result, the segregation of Cu can be suppressed.
[0051] The produced Cu-containing austenitic stainless steel cast slab has suppressed internal defects and is less likely to develop internal cracks during hot working, despite the inclusion of Cu. Furthermore, the Cu-containing austenitic stainless steel cast slab according to the present invention also has excellent cold workability due to the inclusion of Cu. Furthermore, by using the Cu-containing austenitic stainless steel cast slab according to this embodiment, whose chemical composition is controlled within the above-mentioned chemical composition range, it is possible to produce austenitic stainless steel that has excellent hydrogen embrittlement resistance and can be used in high-pressure hydrogen environments, and non-magnetic steel that has excellent corrosion resistance and high strength and can be used in applications where non-magnetism is required.
[0052] Moreover, by using the above-mentioned method for producing a Cu-containing austenitic stainless steel slab, for example, the equiaxed crystal ratio can be made 30% or more. EXAMPLES
[0053] Hereinafter, the embodiment of the present invention will be described in detail with reference to examples. Note that the examples shown below are merely examples of the present invention, and the present invention is not limited to the following examples.
[0054] Using stainless steel materials having the chemical compositions shown in Tables 1 and 2, cast pieces having a thickness of 200 mm and a width of 1250 mm were produced under the following conditions. - Withdrawal speed of molten steel from the mold Vc: 0.4~0.6m / min ·Superheat degree ΔT: 20~40℃ ·Secondary cooling specific water volume: 3~5L / (kg-steel) Electromagnetic stirring position: The part of the slab where the solid fraction in the thickness direction is 0.5 to 0.75 Flow mode: Parallel flow in which the molten steel near the long side flows in the same direction Electromagnetic force pattern: 6 seconds applied, 1 second removed Secondary cooling temperature: up to 800℃
[0055] [Table 1]
[0056] [Table 2]
[0057] For each cast piece, Cr eq and Ni eq Ratio of Cr eq / Ni eq The β value and equiaxed crystal ratio were calculated, and the presence or absence of semi-macro segregation was confirmed.
[0058] Cr eq is the value calculated by the following formula (1), and Ni eq is a value calculated by the following formula (2).
[0059] Cr eq =Cr+(1.37×Mo)+(1.5×Si)…Formula (1) Ni eq =Ni+(0.31×Mn)+Cu+(22×C)+(14.2×N)…Formula (2) In the formulas (1) and (2), Cr, Mo, Si, Ni, Mn, Cu, C, and N represent the content (mass%) of each element.
[0060] The β value is calculated by the following formula (4). β = Cu + (0.0075 × Mn 2 )+(0.0404×Mn)-(0.09×Ni)…Formula (4) In formula (4), Cu, Mn, and Ni are the contents (mass %) of each element.
[0061] The presence or absence of semi-macro segregation was confirmed by the following method. First, the above-mentioned slab was cut in the casting direction of the slab at a position 625 mm from the widthwise end, and an analytical test piece was cut out so that the center was located at 1 / 2 the thickness of the slab on the cross section, the length in the thickness direction and the length in the casting direction were 30 mm, and the thickness (length in the width direction of the slab) was 10 mm. Therefore, the analyzed surface was the surface at the center in the width direction of the slab, including the casting direction and the thickness direction of the slab. The analyzed region was a 25 mm square region whose center was located at 1 / 2 the thickness of the slab on the above-mentioned analyzed surface. The conditions for EPMA analysis were an electron probe microanalyzer (JXA-8230) manufactured by JEOL Ltd., an acceleration voltage of 15 kV, a probe current of 3.25×10 7 A, the beam diameter was 50 μm, the step was 50 μm, and the irradiation time for one step was 40 msec. The Cu content [Cu], Mn content [Mn], and Ni content [Ni] were measured at 500 × 500 points in the center of the thickness direction. The area where the α value was greater than 3.63 was identified by EPMA analysis. The circle equivalent diameter of the identified area was then calculated.
[0062] α=[Cu]+(0.136×[Mn])-(0.2×[Ni]) …Equation (3)
[0063] When a region in which the α value calculated by formula (3) exceeded 3.63 and the area of the region exceeded 1.5 mm2 was confirmed, it was determined that a semi-macro segregation portion was present.
[0064] The equiaxed crystal ratio of the sample was calculated by the following method. That is, the sample was immersed in hydrochloric acid with a concentration of 20 mass% heated to 70°C for 40 minutes to reveal the macrostructure in accordance with JIS G 0553:2019. The thickness of the equiaxed crystal part relative to the thickness of the slab at the width center of the C cross section was taken as the equiaxed crystal ratio.
[0065] The hot workability was evaluated by the following method. A test piece was taken from the prepared sample, with the center located at a position 625 mm from the end in the width direction, and with a length in the casting direction and the length in the cast slab width direction of 200 mm. The thickness of the test piece was 200 mm. The test piece was hot rolled to evaluate the hot cracking tendency at the center of the thickness. In detail, the test piece was heated at 1200°C for 60 minutes, and then removed from the furnace and hot rolling was started. The reduction in area was 20% or more, and the finishing temperature of rolling was 1050°C or more.
[0066] If a crack occurred in the center of thickness during hot rolling, the test piece opened into two plates, and hot rolling was stopped, the evaluation result was poor (×). In addition, after hot rolling was completed, the test piece was cut out at the rolling direction cross section at the width center, and the crack was revealed by PT (penetrant testing), and the length of the revealed crack was measured. If a crack with a width direction length of 10 mm or more occurred at the thickness center on the rolling direction cross section from the cross section, it was judged to be poor (×). After hot rolling was completed, a crack was revealed by PT on the rolling direction cross section at the width center of the test piece, and the crack length was measured, and if the length of the crack from the surface to the thickness center was less than 10 mm, it was judged to be good (◯). The results are shown in Table 3.
[0067] [Table 3]
[0068] As shown in Tables 1 to 3, the Cu-containing austenitic stainless steel cast slab according to the present invention was prevented from internal cracking during hot working.
[0069] Although the preferred embodiment of the present invention has been described in detail above, the present invention is not limited to such an example. It is clear that a person having ordinary knowledge in the technical field to which the present invention pertains can conceive of various modified or amended examples within the scope of the technical ideas described in the claims, and it is understood that these also naturally fall within the technical scope of the present invention.
Claims
1. In mass percent, C: 0.10% or less, Si: 3.0% or less, Mn: 0.1 to 20.0%, P: 0.045% or less, S: 0.0050% or less, Cr: 10.0-25.0%, Ni: 4.0 to 22.0%, Mo: 5.0% or less, Cu: 2.00 to 4.0%, and N: 0.4% or less, with the remainder being Fe and impurities, Cr represented by the following formula (1) eq and Ni represented by the following formula (2) eq Ratio to Cr eq / Ni eq is less than 1.48, In the thickness direction center of the casting direction cross section at the width direction center, there is a region in which the α value represented by the following formula (3) exceeds 3.63, The region has a circular equivalent diameter of 1.5 mm or less, A Cu-containing austenitic stainless steel cast slab having a β value represented by the following formula (4) of 2.51 or less. Cr eq = Cr + (1.37 × Mo) + (1.5 × Si) … Equation (1) i eq (#). α=[Cu]+(0.136×[Mn])−(0.2×[Ni])…Formula (3) β = Cu + (0.0075 × Mn 2 ) + (0.0404 × Mn) - (0.09 × Ni) … Equation (4) In the formulas (1), (2), and (4), Cr, Mo, Si, Ni, Mn, Cu, C, and N represent the contents (mass%) of each element, and in the formula (3), [Cu], [Mn], and [Ni] represent the concentrations (mass%) of each element measured by an electron probe microanalyzer at the center in the thickness direction.
2. The Cu-containing austenitic stainless steel cast slab according to claim 1 , wherein the equiaxed crystal ratio is more than 30%.
3. Instead of a part of Fe, Al: 0.15% or less, Ca: 0.005% or less; and B: 0.005% or less, The Cu-containing austenitic stainless steel cast slab according to claim 1 or 2, comprising one or more selected from the group consisting of:
4. Instead of a part of Fe, Nb: 0.3% or less, or Ti: 0.3% or less, The Cu-containing austenitic stainless steel cast slab according to any one of claims 1 to 3, comprising at least one of the following:
Citation Information
Patent Citations
Austenite antibacterial stainless steel
CN102127718A
Manufacture of fe-ni alloy having excellent suppression effect for striped unevenness at the time of etching
JP1990054743A
Production of austenitic stainless steel excellent in surface condition
JP1996103802A
High strength nonmagnetic steel for fastening linear motor car superconducting coil
JP1997272954A
Cold rolled austenitic stainless steel sheet reduced in amount of springback, and its production
JP1998072644A